Histopathology of the alimentary canal of Anguilla anguilla L. associated with digenetic trematodes: a light and electron microscopic study - SAYYAF DEZFULI, Bahram; ROSSI, Remigio; M. Manera; S. Onestini (Journal of Fish Diseases, 1997)
---